Antixenotic and allelochemical resistance traits of ber (Ziziphus mauritiana) against stone weevil (Aubeus himalayanus) in hot arid region of India (Indian Journal of Arid Horticulture, 2018)
Plants possess different antixenotic and allelochemical properties, which resultantly induce in them different  mechanisms of resistance. The ber varieties/ genotypes Kali, Katha, Illaichi and Tikadi were found to be resistant; Akharota,  Dandan, Gola, Goma Kirti, Sanaur-1, Seb, Umran and ZG-3 moderately resistant; Badami, Banarasi Karaka, Gularvasi, Jogia,  Kaithli, Mundia, Reshmi, Sanaur-3, Thar Bhubhraj, Thar Sevika and Thornless susceptible and Banarsi Pebandi, Chhuhara,  Sanaur-2, Sanaur-4 and Sanaur-5 highly susceptible varieties/ genotypes against stone weevil. The fruit infestation ranged from  8.80 to 49.44 % on retained fruits and 13.31 to 73.77% on dropped fruits. Tannins, phenols, alkaloids and flavonoids contents had  significant negative correlations (P = 0.01) with the percentage fruit infestation on retained fruits and the fallen fruits. The pulp:  stone ratio was having significant positive correlations (P = 0.01) with percent fruit infestation on retained and the dropped fruits.  Two principal components (PCs) were extracted with eigen value =1.0, after varimax rotation with Kaiser normalization  procedure which converged in three iterations. The extraction communalities for all the variables tested were = 0.5 indicating that  the variables were well represented by the extracted PCs which together explained a cumulative variation of 90.75 %. PC1  explained 70.74 % of the variation while PC2 explained 20.01 % of variation. PC1 had the loadings for flavonoid content (0.91),  tannins content (0.71), total alkaloid (0.93) and phenols content (0.95). Pulp: stone ratio of different varieties/ genotypes of ber  (0.96) were loaded in PC2.
Keywords: Ber; antixenotics; allelochemicals; stone weevil; resistance